Transnational Modernity and the Italian Reinvention of Walt Whitman, 1870-1945 - Bernardini, Caterina, 1984- (Book collections on Project MUSE., 2021)
"This study gauges the effects that Walt Whitman's poetry had in Italy in the period from 1870 to 1945: the reactions it provoked, the aesthetic and political agendas it came to sponsor, and the creative responses it facilitated. But it also investigates the contexts and causes of Whitman's success abroad, in the lives, backgrounds, beliefs, and imaginations of the people who encountered it. Ultimately, it chronicles the evolution of a literature intent on regenerating itself and moving toward modernity. Bernardini gives particular attention to women writers and noncanonical writers often excluded from previous discussions of Whitman's Italian reception. The book is grounded in archival studies and examination of primary documents, which led to a series of noteworthy discoveries. While the main focus is on the Italian literary scene, the history of the reception retraced here is constantly evaluated in relation to other cultures that were also intent, in those same years, on reading and recreating Whitman. Studying Whitman's reception from a transnational perspective shows how many countries were simultaneously carving out a new modernity in literature and culture. In this sense, Bernardini not only shows the interconnectedness of various international agents in understanding and contributing to the spread of Whitman's work, but, more largely, a constellation of similar pre-modernist and modernist sensibilities. This stands in contrast to the notion of sudden innovation: modernity was not easy to achieve, and most of all, it did not imply a complete refusal of tradition. Instead, a continuous and fruitful negotiation between tradition and innovation, and not a sudden break with the literary past, is at the very heart of the Italian and transnational reception of Whitman"--